2010
DOI: 10.1111/j.1365-2699.2010.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

A time-calibrated phylogenetic approach to assessing the phylogeography, colonization history and phenotypic evolution of snakes in the Japanese Izu Islands

Abstract: Aim We infer the biogeography and colonization history of a dispersal-limited terrestrial vertebrate, the Japanese four-lined ratsnake (Elaphe quadrivirgata), to reveal the number of times mainland populations have invaded the Izu Archipelago of Japan, the mainland sources of these colonists, and the timescale of colonization. We compare these results with those of past studies in an attempt to uncover general biogeographical patterns. Moreover, we briefly examine the significance of colonization history when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…The Izu Islands were probably formed within the past million years as oceanic islands (Kaneko, Issiki, & Zashu, ). This is consistent with our results as well as the other evolutionary patterns of the endemic organisms of the islands (Kuriyama, Brandley, Katayama, Mori, et al., ). Subclades 4–6 from clade F appear to have migrated from south to north, because the ancestral lineages tend to be distributed in the areas of lower latitude.…”
Section: Discussionsupporting
confidence: 94%
“…The Izu Islands were probably formed within the past million years as oceanic islands (Kaneko, Issiki, & Zashu, ). This is consistent with our results as well as the other evolutionary patterns of the endemic organisms of the islands (Kuriyama, Brandley, Katayama, Mori, et al., ). Subclades 4–6 from clade F appear to have migrated from south to north, because the ancestral lineages tend to be distributed in the areas of lower latitude.…”
Section: Discussionsupporting
confidence: 94%
“…These gene regions have been previously shown to be informative at different levels of divergence within lizards (Leaché & Mulcahy, 2007; Lindell, Méndez‐de la Cruz & Murphy, 2008). Although it has been demonstrated that single locus genetic studies have some limitations (Edwards & Bensch, 2009), mtDNA nonetheless remains useful in exploring geographical relationships among closely‐related species (Pyron & Burbrink, 2009; Daza, Castoe & Parkinson, 2010; Kuriyama et al ., 2011). Primer sequences for ATPase were specifically designed for this project (C2LF4, 5′‐CAATGCTCAGARATYTGYGG‐3′; C3LR, 5′‐GCGTGTGYTTGGTGGGTCAT‐3′), and required an annealing temperature of 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…tigrinus (Tanaka and Ota, 2002). Body size changes of snakes on island populations are generally considered to be associated with a diet alteration related to prey type, prey size, and/or the abundance of prey (e.g., Hasegawa and Moriguchi, 1989; Boback, 2003;Hasegawa and Mori, 2008 Fukada, 1992;Kadowaki, 1996;Kuriyama et al, 2011;Tanaka, 2011;Tanaka and Mori, 2011), Rh. tigrinus (mean SVL, 563-607 mm for males, 630-785 mm for females ;Fukada, 1992;Kadowaki, 1996; also see Moriguchi [1985] for frequency distribution of SVL), and G. blomhoffii (mean SVL, 411-461 mm for males, 422-512 mm for females ;Fukada, 1992;Kadowaki, 1996;Yomeishu Seizo Co. Ltd., 1999), but suggests possible dwarfism in El.…”
Section: Discussionmentioning
confidence: 99%